Correction: Development and Evaluation of a Parenting Resilience Elements Questionnaire (PREQ) Measuring Resiliency in Rearing Children with Developmental Disorders. - PLOS ONE Staff (PLoS ONE, 2015)
[This corrects the article DOI: 10.1371/journal.pone.0143946.].